"Consciousness" during sleep in a TM practitioner: heart rate, respiration, and eye movement - Gackenbach, Jayne; Moorecroft, William; Alexander, Charles; LaBerge, Stephen (My University, 1987)
Reports of consciousness during dreaming or lucid dreaming have been verified by having the dreamer signal from the dream that he/she is dreaming with a prearranged set of distinctive lateral eye movements (LaBerge, 1985). This basic methodology has subsequently been replicated in other sleep laboratories. Relatedly, a continuation of consciousness from the waking state into the sleep state is claimed to be a key aspect of the experience of "Transcendental Consciousness", which is developed by the practice of Transcendental Meditation (TM; Banquet & Sailhan, 1974).
Keywords: lucid dreaming; consciousness; dreamer; eye movements; sleep laboratories; transcendental consciousness; Transcendental Meditation; TM; autonomic arousal; polysomnograms